2006
DOI: 10.1038/sj.emboj.7601125
|View full text |Cite
|
Sign up to set email alerts
|

Displacement of D1, HP1 and topoisomerase II from satellite heterochromatin by a specific polyamide

Abstract: The functions of DNA satellites of centric heterochromatin are difficult to assess with classical molecular biology tools. Using a chemical approach, we demonstrate that synthetic polyamides that specifically target AT-rich satellite repeats of Drosophila melanogaster can be used to study the function of these sequences. The P9 polyamide, which binds the X-chromosome 1.688 g/cm3 satellite III (SAT III), displaces the D1 protein. This displacement in turn results in a selective loss of HP1 and topoisomerase II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 35 publications
2
60
1
Order By: Relevance
“…These histone modifications are features of heterochromatin. Drosophila rDNA genes also show moderate levels of H3K9me (Blattes et al 2006;Peng and Karpen 2007), arguing that heterochromatin-mediated repression is a general feature of rDNA regulation. While the Su(var)3-9 enzyme is one of the major H3K9 methyltransferases for Drosophila heterochromatin (Brower-Toland et al 2009), it is unknown how much histone methylation at the rDNA genes is due to the Su(var)3-9 enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These histone modifications are features of heterochromatin. Drosophila rDNA genes also show moderate levels of H3K9me (Blattes et al 2006;Peng and Karpen 2007), arguing that heterochromatin-mediated repression is a general feature of rDNA regulation. While the Su(var)3-9 enzyme is one of the major H3K9 methyltransferases for Drosophila heterochromatin (Brower-Toland et al 2009), it is unknown how much histone methylation at the rDNA genes is due to the Su(var)3-9 enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…These regions are enriched for heterochromatic proteins that repress transcription and compact chromatin (Hilliker et al 1980). As the rDNA arrays are themselves repetitive, these genes have molecular features of heterochromatin (Blattes et al 2006). Mutations in heterochromatin proteins relieve gene silencing of reporters in heterochromatic regions (Schotta et al 2003), so we tested whether these mutations affected silencing of the X chromosome rDNA array in males.…”
Section: Nucleolar Dominance Is a Genetic Property Of The Y Chromosomementioning
confidence: 99%
“…Another 1982 study by Levinger and myself showed that the D1 protein preferentially binds to (A ϩ T)-rich DNA in vitro, including the 1.672 and 1.688 satellite DNA repeats, and is a component of isolated nucleosomes containing these centromeric satellite DNAs (106). Later studies (107,108) indicated that D1, which contains 10 copies of the "AT-hook" domain, a motif that interacts with the minor groove of AT-rich DNA, is a part of heterochromatin-associated complexes that mediate transcriptional repression.…”
Section: Mdr1 a Multidrugmentioning
confidence: 99%
“…Furthermore, Drosophila embryos undergo homeotic transformations when treated with polyamide drugs that bind a repetitive DNA element to which the GAGA factor binds (20,22). However, establishing if there is a causal or coincidental relationship between repetitive DNA binding, heterochromatic targeting, and biologic response of a site-specific transcription factor has been difficult to address experimentally (1,3,20,(22)(23)(24). In the current study, we identify methods to preferentially block the binding of a transcription factor to repetitive DNA and then follow the effects of that intervention on promoter binding and activation.…”
mentioning
confidence: 99%